Web platform for the calculation of astronomical tide predictions: Implementation for the Buenos Aires maritime coast and its continental shelf. (LACCEI, 2024)
The astronomical tide is a phenomenon that influences complex physical and dynamic processes in the ocean, and practical problems such as port access for ships and the determination of nautical chart datums. Nonspecialized users who require accurate tide predictions for the Argentine coast have only the 51 locations published by the Naval Hydrographic Service in its Tide Tables. This paper describes the operation of the web platform that allows obtaining accurate astronomical tide predictions for any location by entering only the date and the geographic coordinates of interest. The ease of access to the predictions is achieved through the optimization of the calculation for web queries, and the modeling of this phenomenon through empirical or hydrodynamic models. As an example, the region comprising the Buenos Aires maritime coast and its adjacent continental shelf is developed, where the amplitudes and epochs necessary for the calculation of the predictions are obtained from the result of the implementation of the ADCIRC hydrodynamic model for the area, in-situ observations and satellite altimetry.